Protective effects of a compound isolated from Alnus japonica on oxidative stress-induced death in transformed retinal ganglion cells - Jo, Hyoung; Choi, Soon Jung; Jung, Sang Hoon (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Here, we investigated whether hirsutenone, a compound isolated from Alnus japonica, was able to attenuate oxidative stress-induced death in transformed retinal ganglion (RGC-5) cells. Hirsutenone effectively protected RGC-5 cells from oxidative insult induced by, 1-buthionine-(S,R)-sulfoximine (BSO) plus glutamate in a concentration-dependent manner, as demonstrated by propidium iodide (PI)/Hoechst 33342 double staining, flow cytometry, and MTT assays. Moreover, hirsutenone inhibited the increase in apoptotic protein expression resulting from BSO plus glutamate. Hirsutenone also effectively inhibited sodium nitroprusside (SNP)-induced lipid peroxidation in rat brain homogenates. To investigate the effects of hirsutenone in vivo, we used N-methyl-D-aspartate (NMDA) as a negative insult on the retinas of rats. NMDA affects the thinning of the inner plexiform layer (IPL) and causes an increase in the number of terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL)-positive ganglion cells in the ganglion cell layer (GCL). Hirsutenone treatment led to a reduction in NMDA-induced IPL and TUNEL staining of the GCL. In conclusion, hirsutenone isolated from A. japonica may act as neuroprotective agent for conditions such as glaucoma. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: OPEN-ANGLE GLAUCOMA; RGC-5 CELLS; DIARYLHEPTANOID DERIVATIVES; LIPID-PEROXIDATION; ANTIOXIDANT; APOPTOSIS; GLUTAMATE; PROPOLIS; INJURY; DAMAGE